Creating Commons: Reflections on Creating Natural Resource Management Regimes in South Sulawesi, Indonesia - Batiran, Karno; Sirimorok, Nurhady; Verheijen, Bart; Fisher, Micah R.; Sahide, Muhammad Alif K. (Forestry Faculty, Universitas Hasanuddin, 2021)
Thirteen years ago, PAYOPAYO Peasant School Network, an Indonesian community organizing network based in Sulawesi, facilitated Participatory Action Research (PAR) that eventually culminated in a creation of a common resource management regime around an irrigation system for agricultural use in Tompobulu, a village within a national park in upland South Sulawesi. This note from the field presents a reflection on collective action experiences of a community in building the commons in 2008 to 2009, and revisits the extent to which the commons has been managed, how management regimes changed over time, and how it survives as a commons today. The initial factors allowing for establishment of the commons, understood here as a social practice toward common goals, were a shared need for water (local needs & conditions), and the success to make use of the irrigation commons as a means to initiate other collective actions. Drawing from concerted engagement and analysis conducted in 2021, this note revisits the key factors and highlights different ways the commons continues to persist, namely due to the distinct benefits felt by participants, the existence of institutions that regulate the use and maintenance of the commons, the existence of a monitoring system among members, participation of members in formulating and modifying the rules, and the recognition of National Park authorities on the commons and its rules.